New data from the historical bee collection (Hymenoptera, Anthophila) of the Science Museum of the University of Coimbra and additional faunistic updates for Portugal - Hugo Gaspar; Simone Flaminio; Albano Soares; Cristina Rufino; João Loureiro; Sílvia Castro; Thomas J. Wood (Journal of Hymenoptera Research)
Entomological collections hold significant scientific potential, especially understudied taxa of historical collections from important biogeographical regions, such as bees in Portugal. The Science Museum of the University of Coimbra (MCUC) holds the largest historical collection of Portuguese bees, primarily because M.A. Diniz, one of the few Portuguese bee experts, was based in this institution during the 20th century, and several historical collections are stored there from that period and before. Nevertheless, most of the records were unpublished and unrevised. In this work, we revised and databased (via GBIF) 13,374 Portuguese bee records (11,053 unpublished), covering 464 species, of which 11 are new to Portuguese fauna. All 9 type specimens from Portuguese species (1 holotype, 2 syntypes, 5 paratypes and 1 dismissed type) were reported and photographed. We also provide an update of the Anthophila checklist for continental Portugal, with three additional unreported species from other institutions (for a total of 14 new species) and removal or confirmation of exclusion of 19 previously reported species, producing a revised total for the Portuguese continental bee fauna of 736 species.